Mizhuo Guanchangye enema delays the decline of renal function in rats with chronic kidney disease by intervening in the TLR4/MyD88/NF-κB pathway - Li, Han; Xu, Peng; Zhang, Xiaomei; Ye, Naijing; Xu, Fang; Liang, Bo (Frontiers in Medicine, 2024)
Background Chronic kidney disease (CKD) is a prevalent chronic condition that poses a significant threat to human health. There is a close connection between the gut and kidneys, jointly influencing the onset and progression of CKD through the “gut-kidney axis.” Traditional Chinese medicine has shown potential in CKD treatment, but the specific mechanisms require further investigation. Objectives This study aims to explore the protective effects of Mizhuo Enema (MZGCY) on kidney function in CKD rats by regulating the TLR4/MyD88/NF-κB signaling pathway. Methods The researcher employed a CKD rat model, which was divided into four groups: Control, Model, half-dose Mizhuo Guanchangye (1/2 MZGCY), and full-dose Mizhuo Guanchangye (MZGCY). Post enema administration, assessments were conducted on kidney function indicators, which included blood urea nitrogen (BUN), serum creatinine (SCR), and 24-h urinary protein. Additionally, measurements were taken for intestinal toxic substances such as indoxyl sulfate (IS) and lipopolysaccharide (LPS), as well as inflammatory factors interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α). Examinations of pathological changes in both the intestines and kidneys were also performed. During this process, immunofluorescence was utilized to detect the expression levels of proteins toll-like receptor 4 (TLR4), myeloid differentiation primary response 88 (MyD88), and nuclear factor kappa B (NF-κB) in the intestinal tissues. Results It was found that after enema treatment, the BUN, SCR, and 24-h urinary protein levels in the MZGCY and 1/2 MZGCY groups significantly decreased, indicating notable improvement in kidney function. Compared to the model group, the IS, LPS, IL-6, and TNF-α levels in the MZGCY and 1/2 MZGCY groups were significantly reduced. Immunofluorescence showed a marked decrease in the expression of TLR4, MyD88, and NF-κB proteins in the intestines of the MZGCY group. Conclusion MZGCY significantly reduces the levels of intestinal toxins and inflammatory factors in the serum of CKD rats by interfering with the TLR4/MyD88/NF-κB signaling pathway, thereby improving intestinal and renal pathological changes and delaying CKD progression. This study demonstrates that MZGCY has significant renal protective effects, providing a new potential approach for CKD treatment.